Synergistic and Hepatoprotective Effect of Total Glucosides of Paeony on Ankylosing Spondylitis: A Systematic Review and Meta-Analysis - Huang, Yao; Wang, Hui; Chen, Zhe; Wang, Yu; Qin, Kai; Huang, Ying; Shen, Pan; Ba, Xin; Lin, Weiji; Tu, Shenghao (Frontiers in Pharmacology, 2019)
Objective: To conduct a meta-analysis of the efficacy and safety of total glucosides of paeony (TGP) for the treatment of ankylosing spondylitis (AS). Background: TGP is commonly applied as a complementary medicine, especially in combination with disease modifying antirheumatic drugs (DMARDs) and/or nonsteroidal antiinflammatory drugs (NSAIDs) to treat AS in China. Nevertheless, the efficacy and safety of TGP combination treatment still needs more validation. Methods: A systematic literature search was conducted using PubMed, EMBASE, web of science, the Cochrane library, ClinicalTrials, Chinese Biomedical Literature database (CBM), China national knowledge internet (CNKI), Wan Fang medical database and VIP database for available randomized controlled trials (RCTs) investigating the efficacy and safety of TGP on AS up to November 2018. Review Manager 5.3 software and Stata 12.0 software were used to analyze all included studies according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement protocol. Results: Pooled results of 23 RCTs exhibited better symptoms improvement (SI) (95% CI 1.16 to 1.36), lower levels of erythrocyte sedimentation rate (ESR) (95% CI −5.89 to −1.32), C-reactive protein (CRP) (95% CI −5.01 to −1.49), morning stiffness (MS) time (95% CI −3.46 to −1.86), finger to floor distance (FFD) (95% CI −4.80 to −0.86), peripheral joint pain index (PJPI) (95% CI −3.48 to −0.69) and higher level of thoracic expansion (TE) (95% CI 0.18 to 0.40) in TGP group. While Schober test (Schober) showed no significant difference between the two groups. Adverse events (AEs) were significantly decreased (95% CI 0.48 to 0.79) with the usage of TGP. Conclusions: It’s worthwhile to apply TGP as an auxiliary medicine on AS for better efficacy and less side effects, especially when considering the impact of traditional treatment on the liver. Still, further clinical trials with larger sample and better methodological quality are warranted to ascertain the potential benefits of TGP on AS.